139 OLDER PERSONS REHABILITATION: A SIX MONTH PATIENT PROFILE. (18th November 2021) - Black, C; Joyce, O; Armitage, D; McDermott, J; Flynn, B; McDonald, M; O'Hara, C; Costello, M
Abstract: Background: For quality improvement to be assessed in a healthcare setting, understanding the specific patient profile is vital. Only then can system performance and service development be reviewed accurately. The purpose of this review was to analyse the patient profile of a 20 bed older persons rehabilitation unit. Methods: Data was collected weekly for patients admitted and discharged to a sub-acute rehabilitation unit over a six month period (January to June 2021) by a multi-disciplinary team (MDT). Information collected included; age, clinical frailty scale (CFS, revised 2008, Rockwood et al., 2005), MDT involvement, care needs on discharge, onward community referrals and length of stay. Results: 62 patients were included (25 males and 37 females) with an average age of 81 (range 61–99). The CFS was measured for 58 patients and ranged from 1 to 7. On examination, 9% of patients had a CFS of 1–2, 38% a CFS of 3–4, 46% a CFS of 5–6 and 7% a CFS of 7. Of the 62 patients included, all received physiotherapy and occupational therapy, 28 speech and language therapy, 25 dietetics and 48 medical social work. The average length of stay was 42 days (range 10–162). On discharge 42% of patients went home with existing supports, 50% went home with increased supports and 8% went to a residential care facility. Referrals to community services were sent for 65% of patients. Conclusion: 53% of patients admitted to an older person rehabilitation unit had a CFS of 5 or more, indicating they were at least mildly frail. The average length of stay was six weeks and all patients required a minimum of two MDT members during their stay. This highlights the presence of frailty and the importance of effective MDT working in the sub-acute rehabilitation setting.